EXHUMATION OF BASEMENT-CORED UPLIFTS: EXAMPLE OF THE KYRGYZ RANGE QUANTIFIED WITH APATITE FISSION TRACK THERMOCHRONOLGY - Sobel E.R.; Oskin M.; Burbank D.; Mikolaichuk A. (My University, 2006)
The Kyrgyz Range, the northernmost portion of the Kyrgyzstan Tien Shan, displays topographic evidence for lateral propagation of surface uplift and exhumation. The highest, most deeply dissected segment lies in the center of the range. To the east, topography and relief decrease, and preserved remnants of a Cretaceous regional erosion surface imply minimal amounts of bedrock exhumation. The timing of exhumation of range segments defines the lateral propagation rate of the range-bounding reverse fault and quantifies the time and erosion depth needed to transform a mountain range from a juvenile to a mature morphology. New multicompositional apatite fission track (AFT) data from three transects from the eastern Kyrgyz Range, combined with published AFT data, demonstrate that the range has propagated over 110 km eastward over the last ~7-11 Myr. On the basis of the thermal and topographic evolutionary history, we present a model for a time-varying exhumation rate driven by rock uplift and changes in erodability and the timescale of geomorphic adjustment to surface uplift. Easily eroded, Cenozoic sedimentary rocks overlying resistant basement control early, rapid exhumation and exhibit slow surface uplift rates. As increasing amounts of resistant basement are exposed, exhumation rates decrease while surface uplift rates are sustained or increase, thereby growing topography. As the range becomes high enough to cause ice accumulation and to develop steep river valleys, fluvial and glacial erosion becomes more powerful, and exhumation rates once again increase. Independently determined range-normal shortening rates also varied over time, suggesting a feedback between erosional efficiency and shortening rate. Copyright 2006 by the American Geophysical Union.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая